A Micro Tale of a Trade-Off: Structural Change versus Balance-of-Payments Equilibrium in an Egyptian foreign investment project in Algeria - Olivié, Iliana (Revista de Economía Mundial, 2017)
Resource-rich economies can find themselves trapped in a dilemma over whether to prioritize processes of structural change or to preserve their balance-of-payments equilibrium. The objective of national development strategies to diversify the productive structure might reflect on the attraction of foreign direct investment projects, with a negative impact on net exports – therefore leading to current account deficits and increased needs of external financing. This article analyses this macroeconomic trade-off, through the particular case of one Egyptian direct investment in Algeria by way of a cable manufacturing company. The case study is conducted following a previously elaborated methodological framework for the study of the development effects of foreign direct investment (FDI).